2016
DOI: 10.1088/0953-2048/29/10/105002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of notable difference in the field delay times of no-insulation layer-wound and pancake-wound REBCO coils

Abstract: The characteristic magnetic field delay time for a no-insulation (NI) REBCO layer-wound coil is three orders of magnitude longer than that for a NI REBCO double-pancake coil. In a NI layer-wound coil, the circumferential current firstly flows along the periphery of the coil winding, and then it diffuses from the top and bottom turns into the middle turns of the winding, resulting in a long characteristic magnetic field delay time due to the current diffusion process. In contrast, the characteristic magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…Insulated coils -in which the coil is either co-wound with an electrical insulator or the conductor itself has an insulator coating -suffer from stability issues and are prone to damage due to local defects. Non-insulated (NI) coils [4], where the HTS tapes are wound without turn-to-turn insulation, are also actively researched [5][6][7][8][9][10][11] as an alternative. One of the main benefits of such coils is their proven selfprotecting behavior [4,12,13] due alternative current paths via the turn-to-turn resistances.…”
mentioning
confidence: 99%
“…Insulated coils -in which the coil is either co-wound with an electrical insulator or the conductor itself has an insulator coating -suffer from stability issues and are prone to damage due to local defects. Non-insulated (NI) coils [4], where the HTS tapes are wound without turn-to-turn insulation, are also actively researched [5][6][7][8][9][10][11] as an alternative. One of the main benefits of such coils is their proven selfprotecting behavior [4,12,13] due alternative current paths via the turn-to-turn resistances.…”
mentioning
confidence: 99%
“…In comparison to the NI pancake-wound coil, the NI layerwound coil has a longer magnetic field delay time, which has been validated in previous publications [15,16]. However, the layer-wound coil can provide better spatial homogeneity of the magnetic field, which is popular in nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 81%
“…The current in each turn is calculated by an equivalent axisymmetrical circuit model [16,20,40,42], as shown in Figure 1(c) and (d). For the layer-wound coil, the current of each turn can flow into adjacent turns through the contact surface.…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…It has been demonstrated that at steady-state conditions current sharing is determined by the terminal resistances for cables with insulation between tapes [19]- [22]. Different numerical methods and software have been implemented to analyze the electrical behavior of HTS cables [23]- [26].…”
Section: Introductionmentioning
confidence: 99%